2015
DOI: 10.1089/ham.2015.0030
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Tolerance to High Altitude, and Cardiorespiratory Response to Hypoxia

Abstract: Richalet, Jean-Paul, and François J. Lhuissier. Aging, tolerance to high altitude, and cardiorespiratory response to hypoxia. High Alt Med Biol. 16:117-124, 2015.--It is generally accepted that aging is rather protective, at least at moderate altitude. Some anecdotal reports even mention successful ascent of peaks over 8000 m and even Everest by elderly people. However, very few studies have explored the influence of aging on tolerance to high altitude and prevalence of acute high altitude related diseases, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…). There is also evidence to suggest that the manner in which ventilatory responses to acute hypoxia change with age is influenced by sex (Richalet & Lhuissier, ). It would clearly be of interest for future studies to examine different phases of the time course of HPV, sex differences, several different age groups and even different postures (Kovacs et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). There is also evidence to suggest that the manner in which ventilatory responses to acute hypoxia change with age is influenced by sex (Richalet & Lhuissier, ). It would clearly be of interest for future studies to examine different phases of the time course of HPV, sex differences, several different age groups and even different postures (Kovacs et al .…”
Section: Discussionmentioning
confidence: 99%
“…); another concluded that ‘some animal studies show diminution of HPV with ageing, but this has not been demonstrated in humans’ (Lumb & Slinger, ). In contrast to the effect of ageing on the acute hypoxic ventilatory response, which has been examined by several studies, albeit with inconsistent results (Richalet & Lhuissier, ), the impact of ageing on HPV in adult humans is unknown (Swenson, ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, exercise intervention in hypoxia enhances respiratory muscle function through hypoxia‐induced chemoreceptor stimulation and hyperventilation . Adaptation to hypoxia inhibited the activity of the sympathetic nervous system by a decreased excretion rate of norepinephrine and an increase of vagal nerve activity .…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies on obesity and aging have mainly been carried out in Western society, and studies using hypoxic therapy for health promotion of the older adult population are very limited. 3,[14][15][16][17][18] Until now, the majority of obese and aging studies have focused on abdominal or central obesity, hypertension, insulin resistance, high triglyceride and low high-density lipoprotein cholesterol levels, which are associated with metabolic syndrome. 6 The numerous changes in health-related factors that occur during the process of obesity and aging need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation